Stakeholder Pressure and Environmental Disclosure in Southeast Asia’s Mining Companies - Aditya Pandu Wicaksono (Jurnal Dinamika Akuntansi dan Bisnis)
This study examines the potential effect of stakeholder pressure on the environmental disclosure practices of mining companies in Southeast Asia. Stakeholder pressure is represented by environmental regulation stringency, media exposure, and the country’s natural index level. Using the data from 142 mining companies in Southeast Asia for the period of 2017 to 2021, this study finds that stakeholder pressure is a main driver of environmental disclosure in Southeast Asia’s mining companies. This research shows that environmental stringency has a positive association with environmental disclosure. In addition, this study reveals that the higher media exposure of a firm will result in higher environmental disclosure in mining companies. The regression result shows that mining tends to disclose more environmental information when a country has a lower level of the natural index. This study has a significant contribution to the literature and suggests that managers need to fulfill stakeholder demands to maintain the social license.